EVALUASI TERHADAP PERAN PEMERINTAH DALAM PEMBANGUNAN BERKELANJUTAN DESA WISATA PETULU MELALUI PERSEPSI MASYARAKAT - Pande Putu Wulandari; I Gusti Made Dwi Candra Anggara (Universitas Triatma Mulya, 2023)
This research aims to analyze community perceptions of the government's role in the sustainable development of the Petulu Tourism Village, so that relevant stakeholders obtain reflection in order to build a joint consensus. The study of community perceptions is substantial because it aims to evaluate the phenomenon of tourism development in the region and review community actions. This research was designed with a qualitative approach and an interview guide was used as a data collection instrument. Interview activities involving key informants from government elements, community leaders and selected informants in three banjars, namely Petulu Gunung, Nagi and Petulu Desa, as well as non-participant observations were carried out. The research results show that the public perceives positively the role of government as a regulator, facilitator, catalyst and innovator. However, the government's role as a facilitator in efforts to improve technical and managerial competence through training and development activities for the community still needs to be improved.